Magnesium ion doped lithium manganese iron phosphate positive electrode material and preparation method thereof

By doping magnesium ions into the lithium manganese iron phosphate positive electrode material and performing multiple tableting treatments, the problems of poor conductivity and low compaction density of the material are solved, significantly improving its electrochemical performance and cycle life, and suitable for large-scale production.

CN119627097APending Publication Date: 2025-03-14湖北宜化化工科技研发有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576679.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate positive electrode material has problems such as poor conductivity, manganese dissolution, low compaction density and low gram capacity, which affects its commercial application.

Method used

By doping appropriate amounts of magnesium ions, adjusting the unit cell volume, improving the electron conductivity, and improving the compaction density and electrochemical properties of the material through two tableting treatments and high-temperature calcination.

Benefits of technology

It effectively improves the electronic conductivity and compaction density of lithium manganese iron phosphate materials, improves its electrochemical performance and cycle life, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627097A_ABST
    Figure CN119627097A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium ion doped lithium manganese iron phosphate positive electrode material and a preparation method thereof, the chemical formula of the positive electrode material is LiFe < 0.4-x > Mg < x > Mn < 0.6 > PO4, and x is more than 0 and less than or equal to 0.03; the preparation method comprises the following steps: S1, dispersing a lithium source, a manganese source, an iron source, a phosphorus source, a dispersing agent and a magnesium source in water to prepare mixed slurry, grinding, drying, pressing into sheets, and sintering in a protective atmosphere to obtain a precursor; and S2, crushing the precursor obtained in the S1, adding a carbon source, grinding again, drying the material, carrying out secondary tabletting, calcining in a protective atmosphere, and finally crushing, screening and removing iron to obtain the lithium manganese iron phosphate positive electrode material. The lithium manganese iron phosphate prepared by the method is high in compaction density, the capacity is improved after doping modification, and the preparation process is simple and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a magnesium ion-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium iron manganese phosphate (LMFP) has the general formula of LiMn x Fe 1-x PO4, which is an olivine structure crystal, Li + Ions can be embedded and extracted from the crystal to realize the charge and discharge of the battery. Due to its unique structure, the crystal can be kept stable during the process of lithium ion embedding and extraction, which has good stability, thus ensuring the safety and high cycle life of lithium iron manganese phosphate batteries. However, the commercial application of lithium iron manganese phosphate also faces some challenges, such as poor conductivity, manganese dissolution, and low compaction density (2.1-2.2 g / cm 3 ), low gram capacity (135-150 mAh / g), etc. In order to solve these problems, scientific research institutions and enterprises in the industry are actively carrying out technological innovation and process improvement, improving the conductivity, compaction density and structural stability of lithium manganese iron phosphate through doping, coating and other means, and improving its electrochemical performance.

[0003] CN115332516A discloses a magnesium and nickel co-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof, which uses a large amount of organic solvent, has a high raw material price, and is not easy to industrialize and mass produce. Summary of the invention

[0004] The present invention provides a magnesium ion-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof, which can improve the electrical conductivity and compaction density of the positive electrode material, and has a simple production process and is suitable for large-scale production.

[0005] The technical solution of the present invention is to provide a magnesium ion-doped lithium manganese iron phosphate positive electrode material, the chemical formula of which is LiFe 0.4-x Mg x Mn 0.6 PO4,0<x≤0.03.

[0006] In the optional scheme, 0.01≤x≤0.03.

[0007] The present invention also relates to a method for preparing the positive electrode material, comprising the following steps: S1, dispersing a lithium source, a manganese source, an iron source, a phosphorus source, a dispersant and a magnesium source in water to prepare a mixed slurry, grinding and drying, pressing into sheets, and sintering in a protective atmosphere to obtain a precursor; S2: The precursor obtained in S1 is crushed, and then the carbon source is added and ground again, and then the material is dried, and after the second tableting, it is calcined under a protective atmosphere, and finally crushed and sieved to remove iron to obtain the lithium manganese iron phosphate positive electrode material.

[0008] In an optional scheme, the molar ratio of the lithium source, manganese source, iron source, phosphorus source and magnesium source in S1 is 1.0~1.05:0.6:0.37~0.39:1.0:0.01~0.03; the amount of dispersant added is 0.5~2% of the mass of the mixed material.

[0009] Among the optional solutions, at least one of the following conditions is met: The lithium source is one or more of lithium phosphate, lithium dihydrogen phosphate, lithium carbonate, and lithium hydroxide; The iron source is one or more of ferrous oxalate, ferric phosphate, ferric oxide, and ferric oxide; The manganese salt is one or more of manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate and manganese acetate; The phosphorus source is one or more of monoammonium phosphate, diammonium phosphate, phosphoric acid, and lithium dihydrogen phosphate; The magnesium source is one or more of magnesium oxide, magnesium carbonate, magnesium hydroxide and magnesium oxalate; The dispersant is one or more of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and sodium dodecylbenzene sulfonate.

[0010] In an optional solution, when grinding in S1, the particle size D50 is controlled to be 1-5 μm; when grinding in S2, the particle size D50 is controlled to be less than 1 μm.

[0011] In an optional solution, the sintering temperature in S1 is 300-400°C, the holding time is 1-5h, and the protective atmosphere is nitrogen or argon.

[0012] In an optional scheme, the carbon source in S2 is one or more of polyethylene glycol, glucose, sucrose, starch, fructose, maltose, cyclodextrin, citric acid, and polyvinyl alcohol; and the carbon content in the lithium manganese iron phosphate material is 1.0~2.0wt%.

[0013] In an optional scheme, the calcination temperature in S2 is 500-700°C, the holding time is 10-20h, and the protective atmosphere is nitrogen or argon.

[0014] In the optional scheme, when tableting in S1 and S2, the pressure is 5-20MPa and the time is 5-20s.

[0015] The present invention has the following beneficial effects: 1. The positive electrode material provided by the present invention is doped with an appropriate amount of Mn with a radius smaller than Mn during the synthesis process of lithium manganese iron phosphate. 2+ and Fe2 + Mg 2+ , which can reduce the unit cell volume, help stabilize manganese ions, reduce their dissolution, and effectively improve the electronic conductivity of lithium manganese iron phosphate materials. 2+ When overdoped, the material will produce severe lattice distortion, blocking the Li + transmission channel, resulting in a decrease in the conductive properties of the material.

[0016] 2. When preparing the positive electrode material provided by the present invention, in order to ensure that the added Mg 2+ To achieve the expected doping ratio, it has undergone two tableting processes. The first tableting is performed before the raw materials are mixed and calcined, which helps to closely arrange the lithium iron manganese phosphate particles and the magnesium source, so that an ordered crystal structure can be better formed during the subsequent sintering process; after mixing and grinding with the carbon source, the tableting is performed again before calcination to reduce the impact of gas production on the material volume and increase the compaction density of the material. After high-temperature calcination, the lithium iron manganese phosphate forms particles with a certain pore size, which helps to improve the electrochemical properties and cycle life of the material.

[0017] 3. The precursor prepared in the present invention is ground and mixed with a carbon source, dried and pressed into tablets, and then calcined at high temperature. The particles are connected by the carbon source, which serves as a good bridge for electron transfer, improves the defect of poor conductivity of the material itself, and can make the grain growth more perfect, thereby increasing the crystallinity of the crystal and improving the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD pattern of lithium manganese iron phosphate prepared in Example 1.

[0019] Figure 2 This is the charge and discharge curve of lithium manganese iron phosphate prepared in Example 1. DETAILED DESCRIPTION

[0020] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0021] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.

[0022] Example 1 0.102 mol lithium carbonate, 0.12 mol manganese carbonate, 0.076 mol ferrous oxalate, 0.2 mol monoammonium phosphate and 0.004 mol magnesium oxide were dispersed in a certain amount of deionized water with 2% polyvinyl pyrrolidone to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 10 MPa for 10 s and placed in a tubular furnace filled with nitrogen at 300 o C was sintered for 3 hours, and then crushed after cooling. Then 10% glucose was added for the second sand grinding. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 15 MPa for 10 s, and then placed in a tubular furnace filled with nitrogen at 700 o C was sintered for 15 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.38 Mg 0.02 Mn 0.6 PO4 / C positive electrode material.

[0023] Example 2 0.102 mol lithium carbonate, 0.12 mol manganese carbonate, 0.074 mol ferrous oxalate, 0.2 mol diammonium phosphate and 0.006 mol magnesium oxide were dispersed in a certain amount of deionized water with 0.5% polyethylene glycol to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 20 MPa for 5 s and placed in a tubular furnace filled with nitrogen at 300 o C was sintered for 3 hours, and then pulverized after cooling. Then 15% polyethylene glycol was added for a second sand milling to control the particle size D50 to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for a second time at 20 MPa for 5 s, and then placed in a tubular furnace filled with nitrogen at 700 o C was sintered for 15 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.37 Mg 0.03 Mn 0.6 PO4 / C positive electrode material.

[0024] Example 3 0.204 mol lithium hydroxide, 0.12 mol manganese oxalate, 0.074 mol ferrous oxalate, 0.2 mol ammonium dihydrogen phosphate and 0.004 mol magnesium carbonate were dispersed in a certain amount of deionized water with 1% polyvinyl alcohol to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 5 MPa for 20 s and placed in a tubular furnace filled with nitrogen at 350 o C was sintered for 5 hours, and then pulverized after cooling. Then 10% fructose was added for the second sand grinding. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 5 MPa for 20 s. o C was sintered for 20 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.38 Mg 0.02 Mn 0.6 PO4 / C positive electrode material.

[0025] Example 4 0.102 mol lithium carbonate, 0.12 mol manganese carbonate, 0.076 mol ferrous oxalate, 0.2 mol monoammonium phosphate and 0.004 mol magnesium oxide were dispersed in a certain amount of deionized water with 2% polyethylene glycol to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 10 MPa for 10 s and placed in a tubular furnace filled with nitrogen at 350 o C was sintered for 3 hours, and then pulverized after cooling. Then 8% polyethylene glycol was added for a second sand milling to control the particle size D50 to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 10 MPa for 10 s, and then placed in a tubular furnace filled with nitrogen at 700 o C was sintered for 10 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.38 Mg 0.02 Mn 0.6 PO4 / C positive electrode material.

[0026] Example 5 0.105 mol lithium carbonate, 0.12 mol manganese carbonate, 0.076 mol ferrous oxalate, 0.2 mol monoammonium phosphate and 0.002 mol magnesium oxalate were dispersed in a certain amount of deionized water with 2% polyvinyl pyrrolidone to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 10 MPa for 10 s and placed in a tubular furnace filled with nitrogen at 300 o C was sintered for 5 hours, and then pulverized after cooling. Then 8% polyethylene glycol was added for a second sand milling to control the particle size D50 to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 15 MPa for 10 s, and then placed in a tubular furnace filled with nitrogen at 700 o C was sintered for 15 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.39 Mg 0.01 Mn 0.6 PO4 / C positive electrode material.

[0027] Example 6 0.2 mol of lithium dihydrogen phosphate, 0.12 mol of manganese dioxide, 0.038 mol of ferric oxide, and 0.004 mol of magnesium hydroxide were added with 1% of sodium dodecylbenzene sulfonate and dispersed in a certain amount of deionized water to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 15 MPa for 10 s and placed in a tubular furnace filled with nitrogen at 400 o C was sintered for 1 hour, and then pulverized after cooling. Then 10% glucose was added for a second sand milling. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 15 MPa for 10 s, and then placed in a tubular furnace filled with nitrogen for 500 o C was sintered for 20 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.38 Mg 0.02 Mn 0.6 PO4 / C positive electrode material.

[0028] Example 7 0.21 mol lithium hydroxide, 0.04 mol manganese tetraoxide, 0.076 mol iron phosphate, 0.124 mol phosphoric acid, and 0.004 mol magnesium oxalate were dispersed in a certain amount of deionized water with 1% polyethylene glycol to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 15 MPa for 10 s and placed in a tubular furnace filled with nitrogen at 400 o C was sintered for 3 hours, and then crushed after cooling. Then 10% citric acid was added for the second sand grinding. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 15 MPa for 10 s, and then placed in a tubular furnace filled with nitrogen at 600 o C was sintered for 15 hours, and then crushed and sieved to remove iron after cooling to obtain LiFe 0.38 Mg 0.02 Mn 0.6 PO4 / C positive electrode material.

[0029] Comparative Example 1 0.102 mol lithium carbonate, 0.12 mol manganese carbonate, 0.08 mol ferrous oxalate, 0.2 mol diammonium phosphate, and 2% polyvinyl pyrrolidone were dispersed in a certain amount of deionized water to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets at 10 MPa for 10 s and placed in a tubular furnace filled with nitrogen at 300 o C was sintered for 3 hours, and then crushed after cooling. Then 10% glucose was added for the second sand grinding. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was pressed into tablets for the second time at 15 MPa for 10 s, and then placed in a tubular furnace filled with nitrogen at 700 o C is sintered for 15 hours, and then crushed and sieved to remove iron to obtain LiFe 0.4 Mn 0.6 PO4 / C positive electrode material.

[0030] Comparative Example 2 0.102 mol lithium carbonate, 0.12 mol manganese carbonate, 0.08 mol ferrous oxalate, and 0.2 mol diammonium phosphate were added with 2% polyvinyl pyrrolidone and dispersed in a certain amount of deionized water to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min to a particle size D50 less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was directly placed in a tube furnace filled with nitrogen at 300 o C was sintered for 3 hours, and then crushed after cooling. Then 10% glucose was added for the second sand grinding. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was directly placed in a tube furnace filled with nitrogen at 700 o C is sintered for 15 hours, and then crushed and sieved to remove iron to obtain LiFe 0.4 Mn 0.6 PO4 / C positive electrode material.

[0031] Comparative Example 3 0.102 mol lithium carbonate, 0.12 mol manganese carbonate, 0.076 mol ferrous oxalate, 0.2 mol monoammonium phosphate and 0.004 mol magnesium oxide were dispersed in a certain amount of deionized water with 2% polyvinyl pyrrolidone to obtain a mixed slurry, which was sand-milled in a sand mill at 1200 rpm / min until the particle size D50 was less than 5 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was directly placed in a tube furnace filled with nitrogen at 300 o C was sintered for 3 hours, and then crushed after cooling. Then 10% glucose was added for the second sand grinding. The particle size D50 was controlled to be less than 1 μm. The slurry was taken out and placed in a blast drying oven for 80 o C for 12 h, and then the powder was directly placed in a tube furnace filled with nitrogen at 700 o C is sintered for 15 hours, and then crushed and sieved to remove iron to obtain LiFe 0.38 Mg 0.02 Mn 0.6 PO4 / C positive electrode material.

[0032] The positive electrode materials obtained in the above embodiments and comparative examples are mixed with lithium iron manganese phosphate: acetylene black: PVDF = 8:1:1 by mass ratio, and organic solvent NMP is added, stirred into a paste, coated on aluminum foil and dried to make a positive electrode sheet, and a metal lithium sheet is used for the negative electrode; the diaphragm is a polypropylene porous membrane; and a 2023 button half-cell is assembled in a glove box. The battery is tested for charge and discharge cycle performance, and the 0.1C discharge specific capacity is tested within the cut-off voltage range of 2.5 to 4.5V. The electronic conductivity and compaction density tests are all referred to "TCIAPS0029-2023 Lithium Iron Manganese Phosphate Positive Electrode Material for Lithium Ion Batteries". Specific data are shown in Table 1 below. Figure 1 This is the XRD diagram of Example 1. Compared with the standard card, it shows that the target lithium manganese iron phosphate material is synthesized. Figure 2 The charge and discharge curves and cycle performance diagrams of Example 1 at 25°C, 0.1C and 50°C, 1C. It can be seen from the figure that the magnesium-doped lithium manganese iron phosphate material has a first discharge capacity of 155 mAh / g at room temperature 25°C, the manganese-iron ratio is consistent with the expected design, and the capacity retention rate after 60 cycles is 96%. The first cycle discharge capacity of 1C tested at a high temperature of 50°C is 155 mAh / g, and the capacity retention rate after 100 cycles at 1C is 93%, with excellent cycle performance.

[0033] Table 1

[0034] From the data in Table 1, it can be seen that tableting can help improve the compaction density of lithium manganese iron phosphate materials. Tableting alone (Comparative Example 1) and magnesium doping alone (Comparative Example 3) have a certain effect on improving the electronic conductivity of the material. However, after the synergistic effect of two tableting processes and magnesium doping, the electronic conductivity of the powder material has been further improved, which ensures a certain discharge specific capacity and also has excellent cycle performance.

[0035] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A magnesium ion-doped lithium manganese iron phosphate positive electrode material, characterized in that: The chemical formula of the positive electrode material is LiFe 0.4-x Mg x Mn 0.6 PO4,0<x≤0.

03.

2. The positive electrode material according to claim 1, characterized in that: 0.01≤x≤0.03。 3. The method for preparing the positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: S1, dispersing a lithium source, a manganese source, an iron source, a phosphorus source, a dispersant and a magnesium source in water to prepare a mixed slurry, grinding and drying, pressing into sheets, and sintering in a protective atmosphere to obtain a precursor; S2: The precursor obtained in S1 is crushed, and the carbon source is added and then ground again, and the material is dried, and after a second tableting, it is calcined under a protective atmosphere, and finally crushed and sieved to remove iron to obtain a lithium manganese iron phosphate positive electrode material.

4. The preparation method according to claim 3, characterized in that: The molar ratio of lithium source, manganese source, iron source, phosphorus source and magnesium source in S1 is 1.0~1.05:0.6:0.37~0.39:1.0:0.01~0.03; the amount of dispersant added is 0.5~2% of the mass of the mixed material.

5. The preparation method according to claim 3, characterized in that: At least one of the following conditions is met: The lithium source is one or more of lithium phosphate, lithium dihydrogen phosphate, lithium carbonate, and lithium hydroxide; The iron source is one or more of ferrous oxalate, ferric phosphate, ferric oxide, and ferric oxide; The manganese salt is one or more of manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate and manganese acetate; The phosphorus source is one or more of monoammonium phosphate, diammonium phosphate, phosphoric acid, and lithium dihydrogen phosphate; The magnesium source is one or more of magnesium oxide, magnesium carbonate, magnesium hydroxide and magnesium oxalate; The dispersant is one or more of polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and sodium dodecylbenzene sulfonate.

6. The preparation method according to claim 3, characterized in that: When grinding in S1, the particle size D50 is controlled to be 1-5 μm; when grinding in S2, the particle size D50 is controlled to be less than 1 μm.

7. The preparation method according to claim 3, characterized in that: In S1, the sintering temperature is 300-400°C, the holding time is 1-5h, and the protective atmosphere is nitrogen or argon.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The carbon source in S2 is one or more of polyethylene glycol, glucose, sucrose, starch, fructose, maltose, cyclodextrin, citric acid, and polyvinyl alcohol; the carbon content in the lithium manganese iron phosphate material is 1.0~2.0wt%.

9. The preparation method according to claim 3, characterized in that: The calcination temperature in S2 is 500-700°C, the holding time is 10-20h, and the protective atmosphere is nitrogen or argon.

10. The preparation method according to claim 3, characterized in that: When tableting in S1 and S2, the pressure is 5-20MPa and the time is 5-20s.